Adult survival has a stronger role than productivity in the annual population change of European songbirds - Inari Nousiainen; Laura Bosco; Petteri Lehikoinen; Rob Robinson; Juan Arizaga; Jaroslav Cepák; Wolfgang Fiedler; Olaf Geiter; Ian Henshaw; Christof Herrmann; Marc Illa; Henk P. van der Jeugd; et al. (Oecologia, 2025)
Biodiversity is decreasing at an alarming rate, and there is an urgent need to understand the demographic drivers behind population declines. Therefore, it is important to study the different stages of a species’ life cycle, including adult survival and productivity. It is still poorly understood whether adult survival or productivity has a stronger role in population change, and how the role of adult survival and productivity varies spatially in relation to species’ traits. We used bird ringing data from the European Constant Effort Sites (EuroCES) project from the years 2000 to 2021, with 1.2 million captures of 33 songbird species from ten European countries. We investigated the role of productivity and adult survival in annual population change and how it was affected by spatio-climatic gradient (measured as average breeding season temperature per country), migratory strategy (long- vs. short-distance and sedentary birds), and breeding habitat (forest vs. reeds) using linear mixed effect models. Overall, our results show that adult survival is a more important driver of annual population change than productivity within European songbirds. The importance of adult survival and productivity varied spatially, both having a weaker influence in warmer regions. Furthermore, the role of adult survival was stronger for long-distance migrants compared to short-distance migrants. Acknowledging that adult survival has a stronger role in annual population change than productivity can help design more robust conservation actions, especially regarding long-distance migratory songbirds.